Do People Demand Fact-Checked News? Evidence from U.S. Democrats - Felix Chopra; Ingar K. Haaland; Christopher Roth (Center for Economic Studies and ifo Institute (CESifo), 2021)
In a large-scale online experiment with U.S. Democrats, we examine how the demand for a newsletter about an economic relief plan changes when the newsletter content is fact-checked. We first document an overall muted demand for fact-checking when the newsletter features stories from an ideologically aligned source, even though fact-checking increases the perceived accuracy of the newsletter. The average impact of fact-checking masks substantial heterogeneity by ideology: fact-checking reduces demand among Democrats with strong ideological views and increases demand among ideologically moderate Democrats. Furthermore, fact-checking increases demand among all Democrats when the newsletter features stories from an ideologically non-aligned source.
Keywords: D83; D91; L82; 330; fact-checking; news demand; information; media bias; belief polarization